Tool life prediction by response surface methodology in end milling titanium alloy Ti-6A1-4V using uncoated WC-Co inserts - Turnad L., Ginta; A.K.M., Nurul Amin; H.C.D., Mohd. Radzi; Mohd. Amri, Lajis (EuroJournals Publishing, Inc., 2009)
This paper presents an approach to establish models for tool life in end milling of titanium alloy Ti–6Al– 4V using uncoated carbide inserts under dry conditions. Small central composite design (CCD) was employed in developing the tool life model in relation to primary cutting parameters such as cutting speed, axial depth of cut and feed. Flank wear has been considered as the criteria for tool failure and the wear was measured under a Hisomet II Toolmaker’s microscope. Further testing was stopped and an insert rejected when an average flank wear greater than 0.30 mm was achieved. Design-expert version 6.0.8 software was applied to establish the first-order and the second-order model and develop the contours. The adequacy of the predictive model was verified using analysis of variance (ANOVA) at 95% confidence level.